Analisis Pelaksanaan Hospital Information System Dalam Pelaporan Statistik Dasar Rumah Sakit Di Rumah Sakit Jiwa Grhasia Daerah Istimewa Yogyakarta Tahun 2014 - SARI, Ferryana Rusmana; , Ibnu Mardiyoko, SKM., MM; , Arief Kurniawan NP, SKM, M.PH (2015)
The implementation of Hospital Information System has not supported in statistical reporting hospital because the value of BOR, LOS , TOI, BTO is different with IRM. The aim of this studies was to analyze the implementation of Hospital Information System on the hospital statistics. This research method using case study and field research. The subject was 7 participants. The object of this studies is the statistical reports which produced by HIS and IRM. Data collection technique used observation, interviews and focus group discussions. The results showed the weakness of HIS, the values of BOR, LOS, TOI, BTO is contrast to IRM. Men factor, the level of compliance officers to input timely data is not in accordance. Money factor, available budget in HIS but monitoring and evaluation not routinely done. Methods factor, the process of making SHRI is inconsistent. Materials factor, available menu SHRI in the HIS but are not utilized. Machines factor, hardware and software are works fine. Market factor, lack of understanding of statistical data flow system.